Ectoparasitic infestations of the eye: three cases with three different arthropods - Ucan Gunduz, Gamze; Ulutas, Hafize Gokben; Aslanci, Mehmet Emin (The European Research Journal, 2018)
Parasitic infestations of the external eye are uncommon and more often prevalent in tropical and developing countries. We present three cases with ocular infestation caused by three different arthropods admitted to the ophthalmology department of a tertiary health care centre during two months. The first case was infected with the larvae of Oestrus ovis, the second case with Phthiriasis palpebrarum, and the third case with a tick, Ixodes ricinus. All patients in this report were living in city center of Bursa, one of the most industrialized cities of Turkey. Ocular ectoparasitic infestations should be taken into consideration in differential diagnosis of conjunctivitis, blepharitis and eyelid mass, even if patients living in urban areas. Due to the rarity of ocular ectoparasitic infestations and overlapping symptoms with more commonly occuring ophthalmic conditions, a careful ophthalmic examination is required to avoid misdiagnosis and delay in treatment.